2018
DOI: 10.3892/ijo.2018.4576
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-511 inhibits malignant behaviors of breast cancer by directly targeting SOX9 and regulating the PI3K/Akt pathway

Abstract: Numerous studies have revealed that a subset of microRNAs (miRNAs) is aberrantly expressed in breast cancer. The dysregulation of miRNAs is involved in the tumorigenesis and progression of breast cancer due to their negative regulation of downstream target genes. Therefore, the identification of deregulated miRNAs in breast cancer may provide important insights into the diagnosis and treatment of patients with this disease. miRNA-511 (miR-511) has been identified to be deregulated in diverse human cancer types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Previous studies have reported that SOX9 is implicated in the regulation of the PI3K/Akt pathway 31,32. Hence, we next attempted to determine whether miR-605 inhibited the activation of the PI3K/Akt pathway in GBM cells by decreasing SOX9 expression.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have reported that SOX9 is implicated in the regulation of the PI3K/Akt pathway 31,32. Hence, we next attempted to determine whether miR-605 inhibited the activation of the PI3K/Akt pathway in GBM cells by decreasing SOX9 expression.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, PRLR/Jak2/STAT5 is the main signaling pathway for activation in mammary gland, and PRLR-triggered pro-tumorigenic pathways in BC include the PI3K/AKT pathway [172]. As well, numerous studies have shown that IRS4, CDK12, SPC24, Mfng, Transgelin 2, STX3, SOX4, PAK4, TPX2, MEG3 and miR-21, -93, -106b, -130b, -214, -361-5p, -489, -511, -564 as well as lncRNA-HOTAIR and MALAT1 regulate tumorigenesis, proliferation, apoptosis, invasion, migration, paclitaxel resistance or anti-Her2 therapy (trastuzumab) resistance of BC cells through PI3K/AKT pathway [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191]. And then, PI3K/AKT inhibitors have gained wide attentions, and a large number of clinical trials may have provided tremendous promises in the treatment of BC patients (shown in Tables 2 and 3).…”
Section: Nct02240212mentioning
confidence: 99%
“…MiR-511-5p has been studied for its tumor-suppressive role in preventing colorectal cancer cell progression by targeting GPR116 50 and lung adenoma-carcinoma cells by targeting oncogene TRIB2 51 . Also, a study has proven that miRNA-511-5p prevents malignant behaviors of breast cancer with a direct effect on SOX9 and PI3/AKT regulatory pathway 52 .…”
Section: Discussionmentioning
confidence: 99%